Isolation and algicidal characteristics of Citrobacter sp. strain N10 - SUN Pengfei; LU Liling; WANG Guan; ZHAO Yuhua (浙江大学学报. 农业与生命科学版, 2013)
In recent decades, harmful algal blooms (HABs), which are natural phenomena that occur across all the world, have posed threats to decrease dissolved oxygen and have had a negative effect on fisheries, aquaculture, drinking water, tourism and human health. It is increasingly urgent to develop useful strategies for predicting and reducing the negative impacts of HABs. Actually, many methods have been devoted to controlling HABs, including copper sulfate, hydrogen peroxide, ozonization, ultrasonication, collection of algae from water surface using nets, iron powder and magnets, centrifugal separation, or ultraviolet radiation. As an effective and environment friendly strategy to control harmful algal bloom outbreaks, biologic control methods such as using algicidal bacteria against M. aeruginosa have been more and more attractive. It has been demonstrated that algicidal bacteria could serve as potential ways in reducing the impacts of HABs.In this study, a Citrobacter sp. N10 with algicidal activity against the toxic algae M. aeruginosa was isolated and identified from a lake of Zhejiang University using liquid infection technology and 16S rDNA sequence analysis. The growth and algicidal characters of Citrobacter sp. N10 were then studied in order to offer some useful information for HABs controlling.The results showed that the bacterium was gram-negative and its colonies were smooth, convex, low moisture, translucent or opaque and gray, and its colony surfaces were glossy. Sequence analysis of 16S rDNA demonstrated that strain N10 belonged to Citrobacter sp. When inoculation time was 2 to 12 h, N10 grew in logarithmic-growth period, and when inoculation time was beyond 12 h, N10 was in stationary phase. Strain N10 showed a high lysis of M. aeruginosa with an algicidal rate of 86.55% within 24 h. The algicidal rate of N10 increased with increasing incubation time and reached 97.08% within 72 h. pH value had the most significant effect on the growth of strain N10, followed by NaCl concentration and culture temperature, while these three conditions had different effects on algicidal activities of strain N10 against M. aeruginosa. A kind of substance against M. aeruginosa was secreted by strain N10, and the substance was sensitive to high temperature (121 ℃) but resistant to protease K. Relatively speaking, the thalli of strain N10 had hardly algicidal effect against M. aeruginosa. Transmission electron microscope was subsequently used to investigate algal cells' structures after 3 d with treatment of strain N10 cell-free culture filtrate (CCF). The results indicated that the cell membranes and cell walls of M. aeruginosa were broken, while the gas vesicles and some particulate matters such as the cytoplasm phosphate particles and blue bodies disappeared. In addition, the cellular ultrastructure of the photosynthetic lamellae was also found to be disordered and disappeared.In conclusion, the research on the characteristics of N10 against M. aeruginosa can provide a tool in controlling the bloom of M. aeruginosa. The findings are of theoretical significance and potential in reducing the impacts of HABs.